2016
DOI: 10.5070/v427110691
|View full text |Cite
|
Sign up to set email alerts
|

Gopherbusters? A Review of the Candidacy of Barn Owls as the Ultimate Natural Pest Control Option

Abstract: While many raptor species consume rodent pests, the behaviors and habits of barn owls make them particularly suitable candidates for consideration as a viable pest control strategy. As a cavity-nesting species, barn owls will readily nest in man-made structures including nest boxes. Barn owls are also less territorial than many other raptor species and will tolerate other pairs nesting nearby if prey is abundant. Barn owls preferentially consume rodents including voles (Microtus spp.) and pocket gophers (Thomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The mechanisms and nest box characteristics behind colonization, extinction, and persistence (the probability of a box remaining occupied) underlie the ability of barn owls to nest in vineyards and provide meaningful pest control. With remaining uncertainty over the ability of barn owls to control rodent damage (Labuschagne et al 2016, Kross and Baldwin 2016, Johnson et al 2018), a first step for managing their potential for this ecosystem service is confirming our understanding of their nesting preferences both with and without disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms and nest box characteristics behind colonization, extinction, and persistence (the probability of a box remaining occupied) underlie the ability of barn owls to nest in vineyards and provide meaningful pest control. With remaining uncertainty over the ability of barn owls to control rodent damage (Labuschagne et al 2016, Kross and Baldwin 2016, Johnson et al 2018), a first step for managing their potential for this ecosystem service is confirming our understanding of their nesting preferences both with and without disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…These perches are commonly used around the world as a component of ecologically based rodent management (EBRM) (Labuschagne et al, 2016;Sara et al, 2016), and in China they aim to attract raptors to areas of high rodent or pika density (See Fig. 3).…”
Section: Control With Native Predatorsmentioning
confidence: 99%
“…Agricultural extension publications offered suggestions for erecting owl nest boxes (e.g., Heaton et al 2008). Barn owls are an attractive method for pest control because their nest boxes are relatively inexpensive to install and maintain (Kross and Baldwin 2016), and several natural history attributes suggest they could help reduce rodents: adults are not very territorial and can sometimes reach high densities (Smith et al 1974), they are efficient hunters and their broods demand many prey items (Durant andHandrich 1998, Taylor 1994), and in agricultural settings their diets are almost exclusively composed of rodent pests , Taylor 1994.…”
Section: History and Backgroundmentioning
confidence: 99%
“…More recently in California, there is renewed research interest in barn owls as pest control. At the 2016 Vertebrate Pest Control Conference in Newport Beach, Kross and Baldwin (2016) used empirical field data in a predictive model and suggested that a barn owl population density of one nest/10 ha may be able help control an average pocket gopher population, but even the highest barn owl densities would be unable to control abundant and quickly reproducing pocket gopher populations. At the same conference, Browning et al (2016) reported that in Lodi, CA, mound surveys suggested that gophers declined on a vineyard with barn owl boxes relative to a control vineyard without barn owl boxes.…”
Section: History and Backgroundmentioning
confidence: 99%